Determinants of Consumers’ Engagement in Electronic Word-of-Mouth on Facebook - Yap, Wei Chien (2017)
In the last decade, the World Wide Web has revolutionized how user around the world interact with each other. It is not only being a platform for user to connect with different individuals, but as well for daily activities such as daily news about the world and information exchange on vast knowledge and facts. Addition to that, it has become a platform for firms and individual to market their products or brands; trading medium. According to Internet Live Stats (2016), 40% of world population (approximately 4 billion peoples) are connected to the internet and 48% of the internet users are from Asia region as reported in 2013. Since the creation of Facebook in 2004, social networking sites have been an important part of corporate marketing mix. The explosion of information creation and sharing has led to brand marketers and communicators a challenge to overcome. The rapidness of information exchange is overwhelming the consumers’ market that its influence consumers’ selection and purchase behaviour instantaneously. Positive or negative information that diffuse in the Internet could give rise an immense consequence towards a product or brands. With the vast information exchange, consumers have become more susceptible to information and engaging into electronic word-of-mouth communication. On the other hand, brand marketers and communicators wish to engage on these channels to dissemination of information to consumers’ and stimulate purchase intention.